Advancing Engaged Scholarship in the Media Field - Pavlik, John V. (2019)
Policy makers, industry leaders, and concerned citizens alike all face vexing questions about the changing nature of emerging technology and its impact on journalism, media and society. Research on this topic has never been more critical in the U.S. and around the world. The need is especially acute for engaged scholarship in this domain. By bringing their research into the broader public arena, engaged media scholars can contribute to policy debates, shape industry practices and policies, and enrich public understanding.